2016
DOI: 10.1684/epd.2016.0851
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy-associated tumours: what epileptologists should know about neuropathology, terminology, and classification systems

Abstract: Brain tumours are an ever‐challenging issue in neurology and related medical disciplines. This applies in particular to brain tumours associated with childhood‐onset epilepsies, in which seizures are the presenting and only neurological symptom, as our current understanding of the biology and clinical behaviour of an individual tumour is far from being evidence‐based. Prospective and randomized clinical trials are lacking in the field of epilepsy‐associated tumours and a review of the current literature evokes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
42
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 89 publications
(153 reference statements)
3
42
0
3
Order By: Relevance
“…On the other hand, assessment of drug responsiveness may necessitate at least 1 year of observation. 6,7,12,[14][15][16][17][18]23 In fact, although LEATs are usually considered to have a benign indolent behavior, several reports have demonstrated that gangliogliomas (GGs) 3,9,13 and some glial tumors, such as pleomorphic xanthoastrocytoma (PXA), 3,24 may exhibit an evolving course or malignant transformation. 22 Furthermore, in the field of LEATs, where a correct histologic and molecular diagnosis is increasingly important, avoiding loss of time is essential, for epileptologic, neuropsychological, and oncologic reasons.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, assessment of drug responsiveness may necessitate at least 1 year of observation. 6,7,12,[14][15][16][17][18]23 In fact, although LEATs are usually considered to have a benign indolent behavior, several reports have demonstrated that gangliogliomas (GGs) 3,9,13 and some glial tumors, such as pleomorphic xanthoastrocytoma (PXA), 3,24 may exhibit an evolving course or malignant transformation. 22 Furthermore, in the field of LEATs, where a correct histologic and molecular diagnosis is increasingly important, avoiding loss of time is essential, for epileptologic, neuropsychological, and oncologic reasons.…”
mentioning
confidence: 99%
“…1,3,26,27 The group of LEATs is currently enlarging due to newly recognized, often rare, histotypes, such as PXA, angiocentric glioma (AG), papillary glioneuronal tumor (PGNT), extraventricular neurocytoma, 3 • Interobserver variability, surgical strategy (tailored resection), and anatomic site (temporal lobe) are factors related to the incidence of FCD detection • A timely surgical treatment, oriented to optimize epileptologic, neuropsychological, and oncologic outcome should be nowadays warranted and/or mixed features (GG and DNET, PXA and GG, PXA and DNET). 18,23,24,29,30 Knowledge about molecular features of diffuse gliomas 24 and LEATs has grown rapidly. 18,23,24,29,30 Knowledge about molecular features of diffuse gliomas 24 and LEATs has grown rapidly.…”
mentioning
confidence: 99%
See 3 more Smart Citations